EKSPLORASI PROBLEMATIKA DAN MODEL ALTERNATIF OPTIMALISASI ZAKAT DI INDONESIA ERA PEREKONOMIAN MODERN - Nora Maulana; Safwan Safwan; Zulfahmi Zulfahmi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
Even though the potential for zakat in Indonesia presents an astonishing figure of 317 trillion rupiahs per year, Indonesia still has not been able to solve the problem of poverty that haunts the country. This study aims to comprehensively examine the problems and smart solutions to find a new zakat optimization model that is properly implemented to reduce poverty and unemployment in Indonesia. This research is field research using a descriptive qualitative approach design. The research findings reveal several problems that impede the optimal realization of zakat; zakat is not the main priority of government policy, low literacy of the zakat community, the majority of the utilization of zakat is consumptive oriented rather than product-oriented, lack of public trust in the government, low quality of human resources who are professional and competent in the field of zakat, the calculation of zakat is not correct, and negative public perceptions of the zakat profession. The zakat optimization model that can be implemented includes; education on the essence of the zakat paradigm, empowering muzaki, increasing the accountability of zakat management institutions, integrating professional zakat and income tax, innovating productive zakat distribution mechanisms, and building community and government synergy. The results of research findings can become innovations and material for evaluating policies in updating the progress of zakat in Indonesia both at national, provincial or district, or regional central institutions.